Teaching experience on online learning in higher education: Generational analysis - Ni Putu Adelia Kesumaningsari; Jatie K. Pudjibudojo; Maya Hilda Lestari Louk (Intelektual Pustaka Media Utama, 2022)
A transition in learning model implementation occurred in higher education during the COVID-19 pandemic. Online learning answers the needs of long-distance learning. However, not all higher education institutions are thoroughly prepared for online learning. Therefore, this study aimed to understand the online learning experience at higher education institutions from the perspectives of multigenerational teaching staff. This study utilized mixed-method research through a quantitative and qualitative study. A total of 93 participants; male (n=40) and female (n=57) teaching staff filled out a research questionnaire consisting of closed and open questions about online learning. The data were analyzed using descriptive statistics and qualitative thematic analysis. The results indicated positive and negative contributions of the online learning process that affect the effectiveness of online learning according to multigenerational teaching staff perspectives. These findings contribute to the global discussion about the online learning process in higher education and recommend the usage of online learning for teaching staff across generations, complemented with an effective instructional design that would help provide a rigorous learning environment.